World Economic and Financial Surveys : International Capital Markets 1995. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1995)
This paper presents the international financial markets aspects of the current turbulence in emerging markets. The ongoing international diversification of institutional portfolios, the return of flight capital, and the cyclical developments in industrial countries combined to generate a significant volume of capital flows into emerging markets in the developing world. In keeping with developments in global markets, these flows have increasingly been in the form of purchases of tradable bonds, equities, and money market instruments-securities that can readily be sold when sentiments change. The volume of financial wealth that can flee a developing country is now sufficiently large that it can overwhelm any attempt to maintain an exchange rate incompatible with fundamentals. Thus the possibility for investors-domestic and foreign-to exert discipline over policy has strengthened significantly. The resolution of sovereign debt-servicing difficulties has become more complicated with the changes in instruments and participants in international markets.